Lygia Bojunga : a recepção de Corda Bamba por crianças e adolescentes - Schubert, Fernanda Magalhães Boldrin (2007)
The present study describes and analyses how the book "Slack Rope" (1979), Known in Brazil as "Corda Bamba"- written by Lygia Bojunga (1932), was received by the Infantile and Juvenile public. The aim is to contribute theoretically and methodologically to the enlargement of knowledge, regarding the Infantile-Juvenile Literature working in the polemic psychological line, with respect to the human being, which are present in Bojunga´s writings. The present review is justified not only by the concern in investigating polemic themes in the psychological line, but on perceiving the way children and youth react to the learning of living with the loss when reading Bojunga´s book. The outstanding position of the author in Brazilian Infantile-Juvenile Literature has also motivated the studies, once even possessing numberless Dissertations and Thesis Works based on her writings, still opens possibilities for new investigations on her masterpieces. The present study, which is based on theoretical conceptions about Literature, Infantile Literature and the Reader, ruled on both, the Aesthetics of Reception and the Theory of Effect, with the aid of Sociology of Experience by Reading, aims at investigating how 9 - 17 year-old-readers, from a public and a private school in Maringa-PR, have shown their sensibility as human beings, when focusing the death and their stigmata. Their position was studied based on how they filled the gaps in a text. The results proved that reading, in its widest sense, is something more enigmatic than it seems to be, and independently on age or social status, the books by Lygia Bojunga transposes the bridge that ties two extremities: reality and fantasy, raising several feelings in children and adolescents.